The Relationship of Mother’s Work Status and Emotional Mental’s Problem at Preschool Students of TK Annur III Maguwoharjo Sleman Year 2018 - Ratih Handayeni; Evi Nurhidayati (International Journal of Health Science and Technology, 2020)
The problem of children’s growth in preschool age can decrease the human resource quality in the following days when it cannot be detected in early phase. Mother’s assistance of her children is very needed in the first 5 years of golden age. This is the phase where they play and learn with their mother. This study was done to compare between non worker mothers and worker mothers with the problems of emotional mental. The purpose of this study was to identify the relationship of mother’s work status and emotional mental problem at preschool students at TK Annur III Maguwoharjo, Sleman Year 2018. This study was an analytic survey with Cross-Sectional Approach. The independent variable was the problem of emotional mental, and the dependent variable was the mother’s work status. The population in this study involved all workers and non-worker mothers with 149 of students at TK Annur III Maguwoharjo, Sleman while the samples were 140 students. The questionnaire of this study used Emotional Mental Method as a prime data.  The Design of sampling was non probability sampling as a simple consecutive sampling. Statistical analysis for data evaluation were carried out by using Chi Square p= 0.005. The analysis results showed the work status of mothers with emotional mental problems at preschool students at TK Annur III Maguwoharjo, Sleman (P-Value=0.000) with the odd ratio was 415.4; 95% CI; 51.6 to 3339.8. There was significant relationship between mother’s work status and problems of emotional mental at the preschool students of TK Annur III Maguwoharjo, Sleman.